Tetratricopeptide repeat cochaperones in steroid receptor complexes - Smith, David F. (Cell Stress Society International, 2004)
The molecular chaperone machinery contains multiple protein components that have 1 or more structural domains composed of tetratricopeptide repeat (TPR) motifs. Many other proteins of separate or unknown function also have TPR domains, so this motif is not exclusive to molecular chaperones. A general function of TPR domains is to bind other polypeptides, but this otherwise prosaic function has been exploited in an assortment of ways that link chaperones and other protein systems into cooperative networks. Among the best-characterized TPR proteins are several cochaperones that participate in assembly and regulation of steroid receptor complexes. Steroid receptors, members of the nuclear receptor subfamily, are hormone-dependent transcription factors that regulate many vertebrate pathways of homeostasis, growth, differentiation, reproduction, and pathology and, as such, have been of great interest to biologists and clinicians. Moreover, the steroid receptors are among the first recognized native clients for chaperones and have been widely studied models for complex chaperone interactions. To provide a coherent, representative minireview of TPR protein function, the scope of this article has been narrowed down primarily to functions of steroid receptor–associated TPR cochaperones.